Fungsi Administrasi Peserta Didik dalam Meningkatkan Mutu Lulusan Siswa di Madrasah Tsanawiyah An-Najiha Seluma - Hendra Saputra; Retno Ambar Wati (Al-Khair Journal: Management Education, 2024)
Abstract: Student administration has not functioned optimally, characterized by the fact that there are still students who are not able to continue their education to a higher level, there are still students who choose to work rather than continue their education. The purpose of this study is to describe and analyze the administrative function of education in improving the quality of graduates in Madrasah Tsanawiyah An-Najiha Seluma. Using descriptive qualitative methods, data collection techniques using descriptive qualitative methods, data collection techniques through observation, interviews, and documentation. The data analysis technique uses Huberman's theory. The results of the study can be concluded that the administration of students in improving the quality of graduates in Madrasah Tsanawiyah An-Najiha Not functioning optimally, student administration practices are inseparable from various challenges, such as limited resources, both human resources and learning facility resources. To overcome this challenge, the madrasah has adopted a collaborative approach by involving all school residents, including teachers, students, and parents/guardians of students. Therefore, it can be suggested that to overcome the quality problem of student graduates, the Madrasah adopts a collaborative approach with all school residents, including teachers, students, and parents of students, in preparing the planning and implementation of student programs in an effort to improve the quality of student graduates in Madrasah.Keywords: Student Administration Function, Student Graduate Quality, Madrasah Tsanawiyah An-Najiha Seluma. Abstak: Administrasi peserta didik belum berfungsi secara optimal, ditandai dengan masih terdapat siswa belum mampu melanjutkan pendidikan ke jenjang yang lebih tinggi, masih ada siswa memilih bekerja daripada melanjutkan pendidikan. Tujuan penelitian ini untuk mendeskripsikan dan menganalisis fungsi administrasi psesrta didik dalam meningkatkan mutu lulusan di Madrasah Tsanawiyah An-Najiha Seluma. Menggunakan metode kualitatif deskriptif, teknik pengumpulan data menggunakan metode kualitatif deskriptif, teknik pengumpulan data melalui observasi, wawancara, dan dokumentasi. Teknik analisis data menggunakan teori Huberman. Hasil penelitian dapat disimpulkan bahwa administrasi peserta didik dalam meningkatkan mutu lulusan di Madrasah Tsanawiyah An-Najiha belum berfungsi secara optimal, praktik-praktik administrasi peserta didik tidak terlepas dari berbagai tantangan, seperti keterbatasan sumber daya, baik sumber daya manusia maupun sumberdaya fasilitas pembelajaran. Untuk mengatasi tantangan ini, madrasah telah mengadopsi pendekatan kolaboratif dengan melibatkan seluruh warga sekolah, termasuk guru, siswa, dan orang tua/ wali siswa. Oleh karena itu, dapat disarankan bahwa untuk mengatasi masalah mutu lulusan siswa, maka Madrasah mengadopsi pendekatan kolaboratif dengan seluruh warga sekolah, termasuk guru, siswa, dan orang tua siswa, dalam menyususn perencanaan dan pelaksanaan program kesiswaan dalam upaya meningkatkan mutu lulusan siswa di Madrasah.Kata kunci: Fungsi Administrasi Peserta Didik, Mutu   Lulusan Siswa, Madrasah Tsanawiyah An-Najiha Seluma.